2011
DOI: 10.1111/j.1439-0531.2009.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Apoptosis in Aged and Photoregressed Mammalian Seminiferous Epithelium, with Particular Attention to Rodents and Humans

Abstract: Imbalances in the proliferation and apoptosis processes are involved in numerous epithelial alterations. In the seminiferous epithelium, normal spermatogenesis is regulated by spermatogonia proliferation and germ cell apoptosis, and both processes are involved in diverse pathological alterations of the seminiferous epithelium. Other physiological phenomena including aging and short photoperiod, in which apoptosis and proliferation seem to play important roles, cause testicular changes. Aging is accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 72 publications
2
34
1
Order By: Relevance
“…Although in both species this phenomenon is well-known, the Roe Deer has been considered as a species where germ cell apoptosis is not the main mechanism responsible for epithelial atrophy, whereas in Brown Hare apoptosis plays a critical role in such atrophy. In the case of the Syrian hamster, the relationship between apoptosis-proliferation shows a similar behavior to that observed in the Brown Hare in the state of complete regression (Pastor et al, 2011). The detailed study of apoptosis/proliferation ratio in this work allows us to better understand what mechanisms are responsible for testicular atrophy during testicular regression in Syrian hamsters.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although in both species this phenomenon is well-known, the Roe Deer has been considered as a species where germ cell apoptosis is not the main mechanism responsible for epithelial atrophy, whereas in Brown Hare apoptosis plays a critical role in such atrophy. In the case of the Syrian hamster, the relationship between apoptosis-proliferation shows a similar behavior to that observed in the Brown Hare in the state of complete regression (Pastor et al, 2011). The detailed study of apoptosis/proliferation ratio in this work allows us to better understand what mechanisms are responsible for testicular atrophy during testicular regression in Syrian hamsters.…”
Section: Discussionsupporting
confidence: 61%
“…Among such pathological conditions are toxic exposure (Wine et al, 1997;Boekelheide, 2005), growth factor depletion, hormonal alterations associated with gonadotropin and/or androgen deprivation (Woolveridge et al, 1999;Bakalska et al, 2004), treatment with estradiol (Blanco-Rodr ıguez & Mart ınez-Garc ıa, 1997; Chaki et al, 2006), heat exposure (Yin et al, 1997;Paul et al, 2009), cryptorchidism (Ohta et al, 1996;Mizuno et al, 2009), radiation (Meistrich, 1993;Liu et al, 2007), chemotherapeutic treatment (Cai et al, 1997), and vascular ischemia (Turner et al, 1997(Turner et al, , 2004. Among normal physiological conditions, testicular regression owing to photoperiod (a reversible process) and aging (irreversible process) can be included (Pastor et al, 2011). In both cases an imbalance between the phenomena of proliferation and cell death results in depletion of the seminiferous epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to spermatogonia, apoptotic rate of primary spermatocytes, as shown by TUNEL positivity, was significantly elevated compared to controls, which might, in part, explain the mechanism of germ cell loss in aged men [92]. The discrepancy might be due to an age-related deterioration of spermatogonial stem cell niche accompanied by a compensatory decrease in apoptotic spermatogonia [91]. In supporting evidence, a recent histological and ultrastructural study has shown increased apoptosis along with a reduced proliferation in germ cells of the aging testes [93].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 93%
“…Furthermore, high oxidative stress leads to increased apoptosis and spermatozoal DNA damage [79]. Although apoptosis is essential for spermatogenesis under normal conditions, the balance between proliferation of spermatogonia and apoptosis of different germ cell types appears to be disturbed with aging [91]. In spermatogonia of aged men, both expression of Ki-67, a marker of cell proliferation activity, and apoptotic rate were found to be decreased compared to young controls [92].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…Consequently, the cell cycle includes both the cell proliferation cycle and programmed cell death (apoptosis) [1,2].…”
Section: Introductionmentioning
confidence: 99%